Studies On Cleaning Efficiency Of Various Natural Rubber Latex Cleaning Compounds - Dzulkafly, Nuur Syuhada (2018)
Natural rubber latex cleaning compound was prepared by using three types of natural rubber (NR) latex; high ammonia (HA) NR latex, industrial latex compound (ILC) and raw waste latex (RWL). Each of latex types was compounded with two types of cleaning agent which were monoethanolamine (MEA) and diethylene glycol (DEG) at various loadings; 1 per hundred rubber (phr), 3 phr and 5 phr. The mechanical and cleaning effectiveness properties of the NR latex cleaning compound were investigated. Next, HA NR latex cleaning compound at 3 phr of MEA cleaning agent was compounded with calcium carbonate (CaCO3) to investigate the mechanical properties and the cleaning effectiveness of the HA NR latex cleaning compound. The HA NR latex cleaning compound with 30 phr of CaCO3 at 3 phr of MEA was used to determine the suitable application technique which are brush, spray and coagulant spray application technique. Overall, the suitable cleaning agent to be added to the NR latex cleaning compound is MEA at 3 phr and ILC was found to have the best cleaning effectiveness. The mechanical properties of the HA NR latex added with CaCO3 cleaning compound was found to be reduced with the increased of CaCO3. However, the cleaning effectiveness of the HA NR latex cleaning compound was found to be improved with increased loading of CaCO3 and 30 phr of CaCO3 was considered as the optimum loading. Among three different types of application techniques, spray method is found as the best application technique since it gives fastest drying time and better cleaning effectiveness.